DAMPAK KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN BPJS DI PUSKESMAS JATILAWANG KABUPATEN BANYUMAS - Kusumaningtyas Kusumaningtyas (Program Magister Administrasi Publik, Fakultas Ilmu Sosial dan Politik, Universitas Jenderal Soedirman, 2020)
Satisfaction is a feeling that shows a person's happiness or disappointment that comes after comparing the performance (outcome) of the thinking product to the expected performance (or outcome). Quality of service and satisfaction (patient) is a unity that is difficult to separate. To realize the patients’ satisfaction of BPJS at The Primary Health Service (Puskesmas) of Jatilawang Banyumas Regency as public health service owned by the government, in its development is demanded to give good service quality by increasing employee competence and also pay attention to service quality dimension itself. That are reliability, responsiveness, assurance, tangibles, and empathy. This research is a descriptive quantitative research with the cross-sectional approach which aims to know in general about how the level of patient satisfaction. Meanwhile, the specific purpose of this study to determine how much impact the quality of health services to BPJS patient satisfaction. The results showed that in general from the results of the t-test, the variable reliability (X1), responsiveness (X2), assurance (X3), tangibles (X4) and empathy (X5) partially positive and have a significant effect on patients’ satisfaction of BPJS service (Y). Furthermore, the variable reliability (X1), responsiveness (X2), assurance (X3), tangibles (X4) and empathy (X5) simultaneously have a positive and significant effect on BPJS patient satisfaction (Y). Specifically, the amount of BPJS patient satisfaction at The Community Health Center of Jatilawang, Banyumas is equal to 0.992 or 99.2%.